Achieving Reading Equity: A Systematic Program Evaluation of a Reading Intervention Program - Morales Bravo, Brenda; Weis, Charles (Allies for Education, 2019)
In 2012, Laguna Vista School in the Ocean View School District, Ventura County, implemented a program of reading intervention services to struggling readers. The program provides a mix of push-in and pull-out services led by a credentialed teacher and several instructional assistants. This program evaluation was designed to determine the impact of the program created for students who were not reading at grade level. Five years of reading achievement data from the Dynamic Indicators of Basic Early Literacy Skills (DIBELS) and three years of Smarter Balanced Assessment Consortium (SBAC) English Language Arts/Literacy were analyzed to determine program impact. The study found that basic reading skills of students who received reading intervention services grew significant with some effect sizes exceeding two standard deviations. Growth on Common Core State Standard assessments, however, were not as impressive. Recommendations for reading comprehension improvement are provided